A novel grey relational analysis-based committee of machine learning methods for enhanced prediction of coal calorific value - Abiodun Ismail Lawal; Aminat Folorunso Ajeboriogbon; Moshood Onifade; Samson Oluwaseyi Bada; Francois Mulenga (Fuel, 2026)

The distribution and occurrence of rare earth elements (REEs) in coal and industrial scale boiler and gasifier ash - Msizi Mkhize; Nicola Wagner; Samson Bada (Fuel, 2026)

An optimized machine learning framework for prediction of coal abrasive index: Leveraging supervised learning, metaheuristic optimization, and interpretability analysis - Hongning Qi; Jian Zhou; Manoj Khandelwal; Moshood Onifade; Abiodun Ismail Lawal; Chuanqi Li; Samson Oluwaseyi Bada; Bekir Genc (Fuel, 2026)

Optimized design and fabrication of a wind-sifter separator for enhanced dry beneficiation of high-ash coal - Jimmy Alade; Orevaoghene Eterigho-Ikelegbe; Samson Bada (Fuel, 2025)

Predicting the hardgrove grindability index using interpretable decision tree-based machine learning models - Yuxin Chen; Manoj Khandelwal; Moshood Onifade; Jian Zhou; Abiodun Ismail Lawal; Samson Oluwaseyi Bada; Bekir Genc (Fuel, 2025)

Predictive modelling for coal abrasive index: Unveiling influential factors through Shallow and Deep Neural Networks - Moshood Onifade; Abiodun Ismail Lawal; Samson Oluwaseyi Bada; Manoj Khandelwal (Fuel, 2024)

Optimisation of ultrasound-assisted alkali-acid leaching of rare earth elements from run-of-mine and discard coal using the response surface methodology - Agnes Modiga; Jibril Abdulsalam; Orevaoghene Eterigho-Ikelegbe; Samson Bada; Xolisa Goso (Minerals Engineering, 2023)

Correction: Strong, lightweight, thermally stable, and hydrophobic sustainable structural composites produced from coal-based waste and polymer-derived SiOC ceramics - Orevaoghene Eterigho-Ikelegbe; Emmanuel Ricohermoso; Hamza Harrar; Ralf Riedel; Samson Bada (Clean Technologies and Environmental Policy, 2023)

Strong, lightweight, thermally stable, and hydrophobic sustainable structural composites produced from coal-based waste and polymer-derived SiOC ceramics - Orevaoghene Eterigho-Ikelegbe; Emmanuel Ricohermoso; Hamza Harrar; Ralf Riedel; Samson Bada (Clean Technologies and Environmental Policy, 2023)
Recycling coal-based waste (CBW) into composites suitable as a building material might be a necessary response to combat its risk to the environment. Therefore, the objective of this study was to investigate the microstructure and performance of coal composites produced from CBW and polysiloxane polymer (SPR-212). Four types of CBW that differ in physicochemical properties were examined. Fourier transform infrared spectroscopy results indicated that the higher the intensity of the C=C bonds in the CBW, the higher the pyrolysis mass loss and shrinkage experienced by the composites during pyrolysis. The continuous operating temperature of the composites is up to 600 °C. However, at temperatures above 600 °C, composites containing carbon content greater than 36% manifested dramatic degradation. Pyrolysis mass loss in the range of 5.28 to 29.62% was obtained for all the composites. The density range of the composites is between 1.5 and 1.9 g per cubic centimetre. The water absorption of all the composites is within the range of 0 to 25% and is comparable to many building materials. Notably, the composites containing total carbon less than 10% registered a water contact angle greater than 90°, indicating the low wettability of their surface. Furthermore, composites that embodied the highest total carbon (63%) displayed the worst structural property. The findings of this study lay the foundation for further development of high-quality structural coal composites from CBW and the SPR-212 preceramic polymer through optimisation of the processing conditions. Graphical abstract

Adoptable approaches to predictive maintenance in mining industry: An overview - Oluwatobi Dayo-Olupona; Bekir Genc; Turgay Celik; Samson Bada (Resources Policy, 2023)

Mechanism of bonding, surface property, electrical behaviour, and environmental friendliness of carbon/ceramic composites produced via the pyrolysis of coal waste with polysiloxane polymer - Orevaoghene Eterigho-Ikelegbe; Ryan Trammell; Emmanuel Ricohermoso; Samson Bada (Environmental Science and Pollution Research, 2023)
A simple mixing-pressing followed by thermal curing and pyrolysis process was used to upcycle coal waste into high-value composites. Three coal wastes of different physicochemical properties were investigated. The hypothetical mechanisms of bonding between the coal particles and the preceramic polymer are presented. The textural properties of the coals indicated that the lowest volatile coal waste (PCD) had a dense structure. This limited the diffusion and reaction of the preceramic polymer with the coal waste during pyrolysis, thereby leading to low-quality composites. The water contact angles of the composites up to 104° imply hydrophobic surfaces, hence, no external coating might be required. Analysis of the carbon phase confirmed that the amorphous carbon structure is prevalent in the composites compared to the coal wastes. The dc volume resistivity of the composites in the range of 22 to 82 Ω-cm infers that the composites are unlikely to suffer electrostatic discharge, which makes them useful in creating self-heating building parts. The leached concentrations of heavy metal elements from the composites based on the end-of-life scenario were below the Toxicity Characteristic Leaching Procedure regulatory limits. Additionally, the release potential or mobility of the metals from the composites was not influenced by the pH of the eluants used. On the basis of the reported results, these carbon/ceramic composites show tremendous prospects as building materials due to these properties. Graphical Abstract

Systematic physicochemical characterization, carbon balance and cost of production analyses of activated carbons derived from (Co)-HTC of coal discards and sewage sludge for hydrogen storage applications - Gentil Mwengula Kahilu; Samson Bada; Jean Mulopo (Waste Disposal & Sustainable Energy, 2023)
Hydrothermal carbonization (HTC) technologies for producing value-added carbonaceous material (hydrochar) from coal waste and sewage sludge (SS) waste might be a long-term recycling strategy for hydrogen storage applications, cutting disposal costs and solving waste disposal difficulties. In this study, hydrochars (HC) with high carbon content were produced using a combination of optimal HTC (HTC and Co-HTC) and chemical activation of coal tailings (CT), coal slurry (CS), and a mixture of coal discard and sewage sludge (CB). At 850 °C and 800 °C, respectively, with a KOH/HC ratio of 4:1 and a residence time of 135 min, activated carbons (ACs) with the highest Brunauer–Emmett–Teller specific surface ( S BET ) of 2299.25 m 2 g − 1 and 2243.57 m 2 g − 1 were obtained. The hydrogen adsorption capability of the produced ACs was further studied using gas adsorption isotherms at 77 K. At 35 bars, the values of hydrogen adsorbed onto AC-HCT (AC obtained from HTC of CT), AC-HCS (AC obtained from HTC of CS), and AC-HCB (AC obtained from HTC of the blending of coal discard (CD) and SS) were approximately 6.12%, 6.8%, and 6.57% in weight, respectively. Furthermore, the cost of producing synthetic ACs for hydrogen storage is equivalent to the cost of commercial carbons. Furthermore, the high proportion of carbon retained (>70%) in ACs synthesized by HTC from CD and SS precursors should restrict their potential carbon emissions.

Prediction of Thermal Coal Ash Behavior of South African Coals: Comparative Applications of ANN, GPR, and SVR - Abiodun Ismail Lawal; Moshood Onifade; Samson Oluwaseyi Bada; Amtenge Penda Shivute; Jibril Abdulsalam (Natural Resources Research, 2023)

Development of Ag-doped on multi-walled carbon nanotubes for the treatment of fish pond effluent - Saadatu Aliyu; Abdulkareem Saka Ambali; Tijani Jimoh Oladejo; Saheed Mustapha; Titus Chinedu Egbosiuba; Samson Oluwaseyi Bada (Regional Studies in Marine Science, 2023)